Health behaviors of people over 65 in the region of the Lublin Province - Rudnicka-Drożak, Ewa; Olszowy, Jakub; Jankowska, Paula; Jankowski, Krzysztof (Journal of Education, Health and Sport, 2018)
IntroductionThe Polish population is systematically aging. Health behaviors have a significant impact on the health and quality of life of seniors.Objective of the workThe aim of this study was to assess the level of health behaviors among people over 65 living in the Lublin province.Material and methodsThe study was conducted from February 2014 to May 2014, among 80 people over 65, members of Senior Clubs, Universities of the Third Age and patients of the Institute of Rural Medicine in Lublin, living in the Lublin city and rural areas of the Lublin province. The research was conducted using a diagnostic survey - the Inventory of Health Behavior of IZZ Juczyński and a questionnaire constructed by the authors. The obtained results were subjected to statistical analysis using the STATISTICA 13.0 program. Significance of intergroup differences was verified using the Pearson Chi-square test.ResultsThe index of health behaviors for all respondents was on average 83.65, including 87.10 for women and 78.19 for men. Most of the respondents assessed their health condition as good or average, they also undertook physical activity, usually walking. Nearly three quarters of patients complained of circulatory system diseases.ConclusionsThe examined elderly people were characterized by a high level of health behaviors. Women and younger people show more intense health behaviors than men and people from the older age group. Women and people with higher education levels, in the past, statistically more often observed the principles of rational nutrition and lead a healthy lifestyle. Among men, proper eating habits are rated worst, and in the more advanced age category - the positive psychical approach. Most of the respondents take physical activity, commonly walks and bike riding.